DIPLOMACY AND DEFENSE SPATIAL PLANNING - Renaldo Benarrivo; Nala Nourma Nastiti (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2020)
The border issue is one of the important aspects related to the main elements for the establishment of a state. From a defense point of view, the unclear physical and juridical boundaries of the territory will make it even more difficult to carry out border security. Therefore, efforts are needed to resolve land border disputes. The relationship between Indonesia and Timor Leste was marked by land border disputes following Timor Leste, which became a sovereign state. Diplomacy needs to be carried out by the two states, especially for Indonesia to support the ideal defense spatial arrangement. This paper analyzes the relationship between diplomacy and defense spatial planning by taking lessons from the settlement of land border disputes between Indonesia and Timor Leste. Keywords: Defense diplomacy, military diplomacy, border dispute.